Classic Complete Denture-Important Factor Of Social Integration Of Elderly Patient - Dan Nicolae Bosanceanu; Silvia Mihaela Silvas; Dana Gabriela Budala; Roxana Ionela Vasluianu (Romanian Journal of Oral Rehabilitation, 2009)
Attitude toward aging and the elderly was different, however, protection or abandonment, depending on the social ethics of the time. AIM. Paper’s aim is to demonstrate the necessary knowledge of mechanism for adjusting the elderly edentulous to prosthetic treatment, to signal reactivity and responsiveness of the patient to prosthetic treatment total and to social rebalancing of the patient after treatment MATERIAL AND METHOD. In the present work, we made a clinical statistical analysis on a sample of 78 patients, on the individual psycho-somatic adaptation of the elderly with removable dentures This requires close cooperation between the dental team and staff welfare. RESULTS AND DISCUSSION. After analyzing the questionnaires completed and the centralization of data was observed (Table V) that adaptation of the elderly to the complete removable dentures and their acceptance as a a way of reintegration into society and the family was different, younger people accepting with difficulty the mutilation making great efforts to accommodate the return to baseline status, whereas older patients and particularly those with the disorder, accepting themdifficult. CONCLUSIONS. The succes of the removable prosthetic treatment consists in identifying, understanding and meeting the needs of patients in accordance with the criteria and the therapeutic conduct of teh practitioner involves much patience, understanding, good sense and good clinical management issues of the third age.